Highly sensitive type IA fiber Bragg gratings as sensors in radiation environments - Kalli, Kyriacos; Faustov, A. V.; Saffari, Pouneh; Gusarov, Andreï I.; Wuilpart, Marc; Megret, Patrice; Zhang, Lin; Koutsides, Charalambos (My University, 2012)
Type IA fiber gratings have unusual physical properties compared with other grating types. We compare with performance characteristics of Type IA and Type I Bragg gratings exposed to the effects of Co60 gamma-irradiation. A Bragg peak shift of 190 pm was observed for Type IA gratings written in Fibercore PS-1250/1500 photosensitive fiber at a radiation dose of 116 kGy. This is the largest wavelength shift recorded to date under radiation exposure. The Type IA and Type I gratings show different kinetics under radiation and during post-radiation annealing, this can be exploited for the design of a grating based dosimetry system.
Keywords: Bragg peaks; Fiber gratings; Gamma irradiation; Performance characteristics; Photosensitive fibers; Radiation environments; Radiation exposure; Wavelength shift; Dosimetry; Fibers; Ionizing radiation; Fiber bragg gratings